Differential cellular and humoral immune responses in immunocompromised individuals following multiple SARS-CoV-2 vaccinations - Meredith, Rhys T.; Bermingham, Max D.; Bentley, Kirsten; Agah, Sayeh; Aboagye-Odei, Abigail; Yarham, Ross A. R.; Mills, Hayley; Shaikh, Muddassir; Hoye, Neil; Stanton, Richard J.; Chadwick, David R.; Oliver, Maria A. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The heterogeneity of the immunocompromised population means some individuals may exhibit variable, weak or reduced vaccine-induced immune responses, leaving them poorly protected from COVID-19 disease despite receiving multiple SARS-CoV-2 vaccinations. There is conflicting data on the immunogenicity elicited by multiple vaccinations in immunocompromised groups. The aim of this study was to measure both humoral and cellular vaccine-induced immunity in several immunocompromised cohorts and to compare them to immunocompetent controls. Methods Cytokine release in peptide-stimulated whole blood, and neutralising antibody and baseline SARS-CoV-2 spike-specific IgG levels in plasma were measured in rheumatology patients (n=29), renal transplant recipients (n=46), people living with HIV (PLWH) (n=27) and immunocompetent participants (n=64) post third or fourth vaccination from just one blood sample. Cytokines were measured by ELISA and multiplex array. Neutralising antibody levels in plasma were determined by a 50% neutralising antibody titre assay and SARS-CoV-2 spike specific IgG levels were quantified by ELISA. Results In infection negative donors, IFN-γ, IL-2 and neutralising antibody levels were significantly reduced in rheumatology patients (p=0.0014, p=0.0415, p=0.0319, respectively) and renal transplant recipients (p<0.0001, p=0.0005, p<0.0001, respectively) compared to immunocompetent controls, with IgG antibody responses similarly affected. Conversely, cellular and humoral immune responses were not impaired in PLWH, or between individuals from all groups with previous SARS-CoV-2 infections. Discussion These results suggest that specific subgroups within immunocompromised cohorts could benefit from distinct, personalised immunisation or treatment strategies. Identification of vaccine non-responders could be critical to protect those most at risk.